Metaphor Comprehension in Schizophrenic Patients - Rossetti, Ileana; Brambilla, Paolo; Papagno, Costanza (Frontiers in Psychology, 2018)
People with schizophrenia often exhibit difficulties to comprehend figurative expressions, such as irony, proverbs, metaphors and idioms, with a general proneness to neglect the figurative meaning and to accept the more literal one. This inability is usually referred to as concretism and it constitutes a clinical manifestation of the broader language dysfunction called Formal Thought Disorder. The current review focuses on the neuropsychological and neuroanatomical underpinnings of schizophrenics’ misinterpretation of a subgroup of figurative expressions, i.e., metaphors. Metaphors are heterogeneous in nature, classifiable according to various criteria; for instance, metaphors can be conventional and familiar, or conversely, novel and unusual. These linguistic distinctions are substantial because the comprehension of the different types of metaphor entails partially different cognitive strategies and neural substrates. This review gathers studies that have directly investigated which neurocognitive deficits explain the inefficient comprehension of metaphor in schizophrenia. Several impairments have been put forward, such as general intelligence, executive functions and Theory of Mind deficits. Moreover, the neural correlates of metaphor comprehension in schizophrenia, like the left inferior/medial frontal gyrus and the temporal lobe, match those cortices affected by the neuropathology of schizophrenia. Even though the causal defective mechanism is still a matter of investigation, we provide an attempt to integrate existing findings